Antibodies against post-translationally modified vimentin peptides in patients with rheumatoid arthritis - P. A. Kuznetsova; A. L. Maslyanskiy; S. V. Lapin; A. V. Mazing; H. Bang; V. I. Mazurov (Современная ревматология, 2017)
Rheumatoid arthritis (RA) is the most common autoimmune rheumatic disease (ARD) associated with the production of broad-spectrum antibodies, the detection of which is of important diagnostic and prognostic values. The problems of RA diagnosis are associated with the limited sensitivity of currently used serological markers.Objective: to evaluate the diagnostic informative value of autoantibodies against different post-translationally modified (PTM) vimentin peptides in patients with RA and other ARDs.Patients and methods. The frequency of autoantibodies against different isoforms of vimentin was estimated in 144 patients with RA, in 36 patients with other ARDs (ankylosing spondylitis and scleroderma systematica), and in 25 patients of a control group, who had no rheumatic diseases. Antibodies against different PTM vimentin peptides obtained using citrullination, carbamylation/homocitrullination, and acetylation were determined. Anti-citrullinated vimentin (anti-CitVim) peptide, anti-carbamylated vimentin (anti-CarVim) peptide, and anti-acetylated vimentin (anti-AcVim) peptide autoantibodies of IgG and IgA classes were estimated in the serum by enzyme immunoassay.Results. The results of the study showed that IgG and IgA anti-CitVim had the maximum area under the ROC curve (AUC) (0.859 and 0.855, respectively). A slightly smaller AUC was seen in IgG anti-CarVim (0.85), IgG anti-AcVim (0.784), and IgA anti-AcVim (0.651). The diagnostic sensitivity and diagnostic specificity were 66.2 and 96.77% for IgG anti-CitVim, 60.56 and 91.94% for IgA anti-CitVim, 91.55 and 53.23% for IgG anti-CarVim, 63.38 and 93.55% for IgG anti-AcVim, and 49.3 and 70.97%, IgA anti-AcVim, respectively. Positivity for IgG anti-CitVim, IgG anti-CarVim, and IgG anti-AcVim, and anti-IgA CitVim was significantly more frequently detected in patients with RA than in those with other ARDs and in the control group (p<0.05). Thus, the identified autoantibodies against modified vimentin peptides proved to be diagnostically useful serological markers in RA. IgA anti-CarVim and IgA anti-AcVim can also be used in the diagnosis of RA in patients who are seronegative for rheumatoid factor and anti-cyclic citrullinated peptide antibodies.Conclusion. When the upper reference limits are set for IgG anti-CitVim (20 U/ml), IgA anti-CitVim (8.95 U/ml), IgG anti-CarVim (6.25 U/ml), IgG anti-AcVim (17.1 U/ml), and IgA anti-AcVim (9.85 U/ml), antibodies against different isoforms of vimentin are recommended for use as additional laboratory tests to diagnose RA.